Cloning of the fourth functional gene for Protein Phosphatase 1 in Drosophila melanogaster from its chromosomal location. - Dombradi, V.; Mann, D.J.; Saunders, R.D.C.; Cohen, P.T.W. (European Journal of Biochemistry, 1993)
Complementary DNA encoding a catalytic subunit of protein phosphatase 1, PP1 87B, hybridises at four positions (87B, 9C, 13C and 96A) to Drosophila melanogaster polytene chromosomes, three of which are known to be expressed [Dombrádi, V., Axton, J.M., Brewis, N.D., Da Cruz e Silva, E.F., Alphey, L. & Cohen, P.T.W. (1990) Eur. J. Biochem. 194, 739-745]. The fourth gene has been isolated by screening a genomic library of cosmid clones, representing division 13 of the X-chromosome of D. melanogaster, with a PP1 87B probe. This library was constructed as part of the Drosophila genome mapping project [Sidén-Kiamos, I., Saunders, R.D.C., Spanos, L., Majerus, T., Trenear, J., Savakis, C., Louis, C., Glover, D.M., Ashburner, M. & Kafatos, F.C. (1990) Nucleic Acids Res. 18, 6261-6270]. The 5' non-coding region of the isolated gene hybridised to cytological position 13C1-2. By combining reverse transcription and the polymerase chain reaction, the gene was shown to be expressed at a very low level. The PP1 13C gene encodes a protein of 302 amino acids with a predicted molecular mass of 34.5 kDa. It shows 85-94% amino acid identity to the other three protein phosphatase 1 catalytic subunits (PP1 87B, PP1 96A and PP1 9C) described previously, being most closely related to the isoform PP1 87B, which is involved in the control of chromosome separation at cell division and the regulation of chromosome condensation at interphase.